Antibacterial Effect and Physical-Mechanical Properties of Temporary Restorative Material Containing Antibacterial Agents. (29th December 2015) - Mushashe, Amanda Mahammad; Gonzaga, Carla Castiglia; Tomazinho, Paulo Henrique; da Cunha, Leonardo Fernandes; Leonardi, Denise Piotto; Pissaia, Janes Francio; Correr, Gisele Maria
Abstract : Introduction . For the maintenance of the aseptic chain created during the treatment the coronal sealing becomes paramount. Aim . Evaluating the antibacterial effect and the physical-mechanical properties of a temporary restorative material containing different antibacterial agents. Material and Methods . Two antibacterial agents (triclosan and chloramine T) were manually added to a temporary restorative material used as base (Coltosol). The antibacterial action of the material was analyzed using the agar diffusion method, in pure cultures of Escherichia coli (ATCC BAA-2336) and Staphylococcus aureus (ATCC 11632) and mixed culture of saliva collection. The microleakage rate was analyzed using bovine teeth, previously restored with the materials, and submitted to thermocycling, in a solution of 0.5% methylene blue, for a period of 24 hours. The physical and mechanical properties of the materials analyzed were setting time, water sorption, solubility, and compression strength. Results . No marginal leakage was observed for all groups. There was no statistical significant difference in antimicrobial activity, setting time, water sorption, solubility, and compression strength among the materials. Conclusion . The addition of antibacterial agents on a temporary restorative material did not optimize the antibacterial ability of the material and also did not change its physical-mechanical properties.